DESIGN AUTORAL E CULTURA VISUAL: INOVAÇÕES METODOLÓGICAS NO ENSINO DA ARTE - Weymar, Lúcia Bergamaschi Costa (Paralelo 31, 2017)
“Design autoral e cultura visual: Inovações metodológicas no ensino da arte” apresenta projetos de design autoral realizados em Cursos de Design da UFPEL e os vincula ao ensino da arte enquanto práticas relativas à cultura visual e enquanto possibilidade de inovação metodológica. AUTHORIAL DESIGN AND VISUAL CULTURE: METHODOLOGICAL INNOVATIONS IN ART TEACHING The article “Authorial design and visual culture: methodological innovations in art education” presents projects in authorial design, developed in the Visual Design Courses of the Federal University of Pelotas-UFPel, which are related to art education as practices in visual culture, which is seen as a possible methodological innovation.